The Effect of Resveratrol and Static Magnetic Field Interactions on the Oxidation–Reduction Parameters of Melanoma Malignant Cells - Agnieszka Synowiec-Wojtarowicz; Agata Krawczyk; Magdalena Kimsa-Dudek (Applied Sciences, 2023)
Background: Scientific research has confirmed the biological activity of resveratrol, which includes its antioxidant, anti-inflammatory, cardioprotective and anticancer properties. There is no known interaction between a static magnetic field and resveratrol that can modulate resveratrol’s effect on cells. Thus, the main aim of our research was to assess the effect of the co-exposure to resveratrol and a static magnetic field on the oxidation–reduction homeostasis of C32 and Colo829 melanoma cells. Methods: The studies consisted of determining the activity of the antioxidant enzymes that constitute the body’s first line of defense—SOD, GPx and CAT—and determining the lipid peroxidation product—MDA—and the value of the total antioxidant status of melanoma cells. Results and conclusions: Resveratrol was shown to exhibit anticancer properties, possibly through the ferroptosis of melanoma cells. A static magnetic field was also found to abolish the anticancer properties of resveratrol and to have a protective effect against melanoma cells by restoring the redox balance in the cells.